Effect of Punica granatum peel extracts on antimicrobial properties in Walnut shell cellulose reinforced Bio-thermoplastic starch films from cashew nut shells. (15th March 2018) - Harini, K.; Chandra Mohan, C.; Ramya, K.; Karthikeyan, S.; Sukumar, M.
Highlights: Cashew nut shell starch and Walnut shell cellulose were extracted and characterized. CNS starch was found to be a good source for bioplastic production. Walnut shell cellulose was examined to be a good reinforcing material. 2% WN cellulose reinforced CNS starch films were found to have good mechanical property. Pomegranate peel was examined to be a good source of active compounds. Abstract: The main aim of the present study is to extract and characterize cashew nut shell (CNS) starch and walnut shell cellulose (WNC) for development of cellulose reinforced starch films. Moreover, the extraction and characterization of pomegranate peel extract, for incorporation with CNS-WNC films, was investigated. CNS starch was examined to be a moderate amylose starch with 26.32 ± 0.43% amylose content. Thermal degradation temperature of CNS starch was found to be 310 °C. Walnut shell cellulose was found to have high crystallinity index of 72%, with two thermal degradation temperatures of 319 °C and 461 °C. 2% WN cellulose reinforced CNS starch films were examined to have good oxygen transfer rate, mechanical and physical properties. Thermal degradation temperature of CNS-WNC starch films were found to be at the range of 298–302 °C. Surface roughness of CNS-WNC starch films were found to be increasing with increase in concentration of cellulose in films. Hydroxymethylfurfurole, Benzene, 2-methoxy-1, 3, 4-trimethyl and 1, 2, 3-Propanetriol, 1-acetate were found to be major active compounds present in hydrophilic extracts of Punica granatum peels. 2% WN cellulose reinforced starch films infused with hydrophilic active compounds of pomegranate peel was examined to be having good active package properties.